Pemberian Hidroterapi pada Pasien Hipertensi (Window of Nursing Journal, 2025)
Hypertension is a condition where the systolic blood pressure is more than or equal to 140 mmHg and the diastolic blood pressure is more than or equal to 90 mmHg after taking two or more measurements. This study aims to determine the effect of hydrotherapy on reducing blood pressure in hypertensive patients in the working area of the Bangkala Health Center, Makassar City. This study uses a quasi-experimental research design and the research design is one group pretest- posttest. This study used one intervention group. The samples used in this study were 16 people who had hypertension. The treatment group will be given hydrotherapy for 15 minutes with warm water temperature of 38-40oC every day for 7 days every morning. Data analysis used paired t-test. The statistical test results of the hydrotherapy treatment were effective in reducing blood pressure with a p value